THE USE OF CASE TECHNOLOGIES IN TEACHING STUDENTS - Yuliya M. Tsarapkina (Образование и наука)
Аbstract. The aim of the article is to consider the possibilities of use of case technologies in educational process of the university; to prove the efficiency and perspectivity of the given method while training the future expertsprofessionalsMethods. Retrospective and abstract analyses of the scientific-theoretical and practical literature are used while describing the history of development of case-study technology and its didactic possibilities. Test materials are used as the measuring tool of dynamics of informative activity of students, changes of level of their knowledge and abilities in the process of skilled-experimental work.Results and scientific novelty. The way of formation of concept «case technology» is shown; examples of various approaches to understanding of the given method are given; author's experience of research of the given problem is described; stages of work with case technology are allocated. It is experimentally proved that case technologies not only help to fix subject knowledge, to find professional the competence, but also promote development of creative thinking, and form skills of behaviour in a group: abilities to operate in a team, to state and defend the point of view, to listen, to carry on dialogue, to ask questions, to operate with the knowledge, building logic schemes of the problem solution. Besides, during the training period using a case technology students study independent ways of knowledge acquisition which are necessary for the modern professional in constantly ever-changing economic and social realities.The case method reveals creative potential, learns to think and operate differently not only students, but also teachers. This method promotes democratisation of educational process, formation of teachers’ progressive thinking, raises motivation of pedagogical activity.Practical significance. The article provides conclusions and recommendations for the use of case technologies in the educational process at the university.